THU0479 The antiosteoporotic treatment is scarce among patients with vertebral fracture reflected in the radiological report: data from a fracture unit-fls. (12th June 2018) - Pons-Bas, A.; Rosas, J.; Hernández, M.; Cano, C.; Ivars, E.; Lorente, M.; Hernández, J.; Santos-Soler, G.; García, A.; Salas, E.; Arcos, H.; Senabre-Gallego, J.M.; et al.
Abstract : Background: A relevant number of patients with vertebral fracture (VF) do not receive specific treatment for osteoporosis and remain as invisible fractures. The objective of the Fracture Units-FLS is to detect patients with fracture, to perform an adequate diagnostic evaluation, initiate treatment and try to prevent new fractures. Objectives: To know the characteristics of the patients and attitude of the referring service, in which the radiological report identifies the presence of VF. Methods: Observational study carried out from January 1 to June 30, 2017, of consecutive patients in which the radiological report after performing simple radiology or CT, reflects the presence of dorsal, lumbar or both VF. The attitude of the service requesting the radiological test was reviewed 3 months after the radiological report. The following variables were collected: general data of the patients (age, gender), the service requesting the imaging test (specialty, request from hospitalisation or ambulant, diagnosis and/or previous treatment for osteoporosis, attitude towards the FV) and the radiological test (type of test and location of the VF). Results: 91 patients were included, of which 62% were women, with a mean age of 72±11.56 years. In 46% of the patients, the image test was requested by one of the Internal Medicine Services (gastroenterology: 31%, oncology-haematology: 17%, rheumatology: 14%, neumology: 12%, cardiology: 10%), 36% by Primary Care Physicians, 15% from the Emergency Department of the Hospital and the remaining 2% from a Surgical Service. In 77%, the radiological test was given to ambulatory patients. In 56%, the imaging test was simple radiology (chest X-ray: 56%, dorsal-lumbar spine: 41% and the remaining 4% bone series study) and 44% CT. In 61%, the fracture was located in dorsal spine, in 28% in lumbar spine and the remaining 11% in the dorsal and lumbar spine. Previously, 44% were diagnosed with osteoporosis and 38% were undergoing specific treatment (oral bisphosphonate: 23%, bisphosphonate iv: 20%, denosumab: 20%, SERM: 8%, PTH: 6% and only calcium +vitamin supplements D: 23%). Three months after the identification of the VF, 66% did not receive specific treatment for osteoporosis, 11% were referred to Rheumatology (initiating treatment in all) and 3% to Traumatology. Three (3%) of the patients had died and 2 (2%) had moved away. Conclusions: Despite being reflected in the radiological report, a significant number of patients with vertebral fracture do not receive antiosteoporotic treatment, 3 months later. Acknowledgements: The study was supported with a research grant from the Association for Research in Rheumatology of Marina Baixa (AIRE-MB). Disclosure of Interest: None declared